Universal Antibody Conjugation to Nanoparticles Using the Fc gamma Receptor I (Fc gamma RI): Quantitative Profiling Of Membrane Biomarkers - Kim, Chloe; Galloway, Justin F.; Lee, Kwan Hyi; Searson, Peter C. (AMER CHEMICAL SOC, 2014)
Antibodies are a class of molecules widely used in bioengineering and nanomedicine for applications involving protein recognition and targeting. Here we report an efficient method for universal conjugation of antibodies to lipid-coated nanoparticles using radially oriented Fc gamma RIs. This method is performed in physiological solution with no additional coupling reagents, thereby avoiding problems with antibody stability and functionality. Coupling to the Fc region of the antibody avoids aggregation and polymerization allowing high yield. In addition, the antibody is oriented perpendicular to the surface so that the binding sites are fully functional. Using this method we demonstrate quantitative profiling of a panel of four membrane-bound cancer biomarkers (claudin-4, mesothelin, mucin-4, and cadherin-11) on four cell lines (Panc-1, MIA PaCa-2, Capan-1, and HPDE). We show that by designing the lipid coating to minimize aggregation and nonspecific binding, we can obtain absolute values of biomarker expression levels as number per unit area on the cell surface. This method is applicable to a wide range of technologies, including solution based protein detection assays and active targeting of cell surface membrane biomarkers.
Keywords: PANCREATIC-CANCER; QUANTUM DOTS; GENE-EXPRESSION; CELL LINES; MULTIFUNCTIONAL NANOPARTICLES; IGG-BINDING; PROTEIN-A; ADENOCARCINOMA; CLAUDIN-4; MUC4